Onychomycosis among cancer patients undergoing chemotherapy in Tehran, Iran: a cross-sectional study - Fatemeh Fathi; Farhad Shahi; Alireza Khosravi; Zahra Saffarian; Nader Safarian; Mir Saeed Yekaninejad; Zoha Shaka (Iranian Journal of Microbiology)
Background and Objectives: Due to the persistence of residual fungal elements, onychomycosis tends to have a high recurrence rate. It is essential to determine the etiology and frequency of onychomycosis across various factors. This study aimed to assess the prevalence of onychomycosis and identify its fungal agents in cancer patients undergoing chemotherapy. Materials and Methods: This cross-sectional study was conducted on cancer patients attending the Oncology Clinic and Cancer Institute of Tehran University of Medical Sciences. Among the 165 patients meeting the inclusion criteria, 75 individuals with nail alterations were referred to a dermatologist. Each patient's information, including demographics, disease-related data, and details about nail involvement, was recorded. When onychomycosis was suspected, nail samples were collected from the deepest part and examined using a light microscope after clarifying with 15% potassium hydroxide (KOH) to detect fungal elements. Results: The prevalence of onychomycosis was 37.6% (n=62). Among the 75 patients with nail alterations and suspected onychomycosis, 17.3% (n=13) tested negative for pathogenic agents. The most common pathogen was Candida albicans, present in 21% (13/62) of patients with positive onychomycosis. The prevailing nail alteration was onycholysis, affecting 45.3% (34/75) of patients. Conclusion: Onychomycosis exhibits associations with variables such as gender, age, cancer and chemotherapy.